Cover Image, Volume 69, Issue 3. Issue 3 (10th January 2021) - Huerga‐Gómez, Alba; Aguado, Tania; Sánchez‐de la Torre, Aníbal; Bernal‐Chico, Ana; Matute, Carlos; Mato, Susana; Guzmán, Manuel; Galve‐Roperh, Ismael; Palazuelos, Javier
Abstract : Cover Illustration: Tetrahydrocannabinol administration at early postnatal ages to CNP ‐mGFP mice increases mature myelinating oligodendrocyte cell density in the developing white matter. CNP (2′, 3′‐Cyclic nucleotide 3′‐phosphodiesterase; green) and MAG (myelin‐associated glycoprotein; red). (See Huerga‐Gómez, A. et al, https://doi.org/10.1002/glia.23911 .)